2019
DOI: 10.1111/1471-0528.15854
|View full text |Cite
|
Sign up to set email alerts
|

The vaginal microbiota, human papillomavirus and cervical dysplasia: a systematic review and network meta‐analysis

Abstract: Background Persistent infection with high-risk human papillomavirus can lead to cervical dysplasia and cancer. Recent studies have suggested associations between the composition of the vaginal microbiota, infection with human papillomavirus (HPV) and progression to cervical dysplasia and cancer.Objective To assess how specific cervico-vaginal microbiota compositions are associated with HPV infection, cervical dysplasia and cancer, we conducted a systematic review and network metaanalysis (registered in PROSPER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
219
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(270 citation statements)
references
References 55 publications
15
219
2
2
Order By: Relevance
“…Similarly to the previous studies [2,4,17,18,23,24,40,42,47], we found increased abundances of several anaerobic bacteria such as Prevotella, Bacillus, Anaerococcus, Sneathia, Megasphaera, Streptococcus and Anaerococcus in HPV-infected women. We recognized Megasphaera of Firmicutes phylum as the most signi cant genus related with HPV infection, while Lee et al identi ed Sneathia spp.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similarly to the previous studies [2,4,17,18,23,24,40,42,47], we found increased abundances of several anaerobic bacteria such as Prevotella, Bacillus, Anaerococcus, Sneathia, Megasphaera, Streptococcus and Anaerococcus in HPV-infected women. We recognized Megasphaera of Firmicutes phylum as the most signi cant genus related with HPV infection, while Lee et al identi ed Sneathia spp.…”
Section: Discussionsupporting
confidence: 89%
“…However, L. iners has many properties different from other Lactobacillus spp., for example unable to produce H 2 O 2, and it often predominates in the presence of HPV infection [4,17,18] and CIN [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This nding contradicts the well-known evidence that Bacterial vaginosis and sexually transmissible infections are associated with persistent high-risk human Papillomavirus and precancer. [30,31] It is possible that reporting bias may have affected the analysis for vaginal infection given that over 80% of the women in the sample reported having vaginal infection. This is possible since, anecdotally, women in our population often perceive vaginal discharge as "toilet" infection.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Do these changes affect the vaginal microbiome and its relationship with HPV infection? [28][29][30] Is HPV entry at the vaginal epithelium basal layer following LASER easier? 31,32 These are important questions that research needs to address.…”
mentioning
confidence: 99%